Inhaled budesonide does not prevent acute mountain sickness after rapid ascent to 4559 m - Berger, Marc Moritz; Fried, Sebastian; Bärtsch, Peter; Mairbäurl, Heimo (The European respiratory journal, 2017)
Prophylactic inhalation of budesonide does not prevent acute mountain sickness after rapid ascent to high-altitude http://ow.ly/Bc9p30dOz46
Gesehen am 27.04.2018